Glucose Monitoring Technologies and Challenges: An Update - Bisht, Deepali; Yadav, Vedika; Rajsi; Saha, Panchali; Kumar, Narendra (The International Journal of Biotechnology, 2019)
The innovation of glucometer has set a benchmark to restrain the effects of diabetes. Diabetes is a scourging metabolic disorder, responsible for disabilities and anachronistic deaths among mass populations. The hyperglycemic condition creates physiological and psychological sufferings to the patients. These complications have led to drastic evolvement in the diabetes diagnostic technologies. The pioneer work in the field of glucose monitoring devices started with the development of blood-based sensing practices, extensively used by the patients but it is an invasive technique which induces trouble in the subjects. Thus, a non-invasive, painless method of glucose testing is a new advancement in the range of glucometers and would profoundly increase the compliance and overcome complications. Saliva-based glucometers is a non-invasive approach, has the potential to exceptionally overcome the discomfort brought up by the blood-based invasive methods. The objective of presenting this review is to provide the chronological series of events in the identification of the disease along with the technological advancements in the glucose monitoring devices.